Estudo da avaliação no disparador de aprendizagem Simulação Laboratório Morfofuncional/Faculdade de Enfermagem/UFPel - Santos, Mateus Casanova dos (2010)
This paper derives the dissertation research entitled "Study on the evaluation of trigger learning Simulation - Morphofunctional Lab / College of Nursing / UFPel" and is characterized by a case study of investigative and descriptive participant character, from the educational experience in the trigger Learning Simulation in Nursing, the second half of the first cycle graduate of the College of Nursing, Federal University of Pelotas (UFPel), which develops simulation of clinical semiology and semiotics in Nursing. The goal was to understand the assessment in the practice of simulation - Lab Morphofunctional in the context of the process of curricular reorganization of the College of Nursing / UFPel, contributing to the improvement process of planning teaching and evaluation of trigger learning that integrates the new curriculum graduate of the College of Nursing / UFPel, initiated in 2009. From the initial reflections of this study, there is the theory of Bernstein as a powerful tool Semiologic of teaching practices, which contributes to the planning and analysis of the evaluation of the device under study educational curriculum. In this pedagogical context, we observed the internal classification of the regulative and instructional discourse strengths.